Back to the Sources. Manfredo Tafuri’s Teorie e storia dell’architettura (1968) between Project and Work in Progress - Capponi, Marco (Histories of Postwar Architecture, 2020)
A rigorous study of Manfredo Tafuri (1935-1994) must inevita-bly find compensatory strategies to overcome the main difficulty posed by the object of study: that of the sources. A challenge, we might say, made even more difficult by the fact that Tafuri, with rare exceptions, never included bibliographies in his books.This contribution intends to present the first results of a philolog-ical analysis on one of the most important books in the historian’s œuvre and the debate of the time, Teorie e storia dell’architet-tura (1968), closely compared with its second Italian edition (1970). This first step and the significant discovery of the letters exchanged in 1967-69 between Tafuri and the publishing house let to detect the extent to which Tafuri originally modified the book’s project and intervened in its re-editions. This leads to the conclu-sion that he refashioned himself and politicised his work retroac-tively, probably to approach the new Venetian intellectual context.Moreover, the systematic filing of 1968 book’s bibliography, together with the critical bibliographies and recordings from his mid-1960s lectures, allow to give due weight to references hitherto unknown. They help us to enter into the historiographic framework in which the main problem – the relationship with history – is to be situated, and to identify a number of knots on which Tafuri will focus in the following years.The analysis situates Teorie e storia in 1960s artistic and archi-tectural discourse and brings to light, in particular, the underlying conversation with Emilio Garroni’book La crisi semantica delle arti (1964), a source that fits precisely a generational urgency, that of architecture and its meaning, to which Tafuri will constantly return.The reading is intertwined with a parallel narration through the illustrations replaced by Tafuri for the second edition of Teorie e storia.